2001
DOI: 10.1038/sj.ijo.0801635
|View full text |Cite
|
Sign up to set email alerts
|

Leisure-time physical activity and regular walking or cycling to work are associated with adiposity and 5 y weight gain in middle-aged men: the PRIME Study

Abstract: OBJECTIVE:To examine the in¯uence of physical activity on body mass index (BMI), waist circumference (W) and body mass changes (DBMI) in middle-aged men, with special regard to moderate-intensity activities. DESIGN: Longitudinal study of adults who participated in the PRIME Study. SUBJECTS: A cohort of 8865 men aged 50±59 y, free of coronary heart disease. MEASUREMENTS: BMI and W at baseline, body mass changes over a 5 y period. Detailed baseline assessment of net energy expenditure due to physical activity (P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
71
0
3

Year Published

2004
2004
2019
2019

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 120 publications
(79 citation statements)
references
References 27 publications
5
71
0
3
Order By: Relevance
“…This is consistent with previous studies showing a negative relationship between obesity indices and vigorous activities or high levels of energy expenditure through physical activity. 6,58 Littmand et al 11 found that high-intensity activities (such as fast walking, fast cycling, jogging, aerobics) were inversely associated with weight gain in both sexes, whereas the association was not statistically significant with low-intensity activities, such as slow walking, slow cycling and swimming. In this study, associations between physical activity and sedentary behavior patterns and overweight were stronger for women than for men.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This is consistent with previous studies showing a negative relationship between obesity indices and vigorous activities or high levels of energy expenditure through physical activity. 6,58 Littmand et al 11 found that high-intensity activities (such as fast walking, fast cycling, jogging, aerobics) were inversely associated with weight gain in both sexes, whereas the association was not statistically significant with low-intensity activities, such as slow walking, slow cycling and swimming. In this study, associations between physical activity and sedentary behavior patterns and overweight were stronger for women than for men.…”
Section: Discussionmentioning
confidence: 99%
“…Although the optimal level of physical activity that would prevent weight gain is still debated, 60,61 these data are in agreement with the notion that even in the absence of high-intensity physical activity, some energy expended during leisure time may be beneficial for weight control. 6 In addition, it may be easier to incorporate into daily life multiple activities of relatively short duration.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In multiple studies, individuals who exercise gain less weight over time both after a planned weight loss and without any prior attempts at weight change. [46][47][48][49] Exercise may also allow adaptation to a highfat diet, thereby specifically modifying the proposed relationship between dietary fat and weight gain. 50 Our activity measure was limited to three categories in analysis (sedentary, moderate, and vigorous) and thus may not have adequately captured true activity levels.…”
Section: Macronutrient Composition Of Diet and Weight Change CL Moscamentioning
confidence: 99%
“…Regarding somatic symptoms, physical activities are able to prevent loss of muscular mass and strength and minimize the risk of fractures and the compromising of quality of life of subjects in the age group (19,20) . Moreover, they contribute to the increase of cardiorespiratory fitness (19,21) as well as bone mineral density (22) , besides improving the lipid profile (23) and reducing the percentage of fat and its markers (24) , which are somatic characteristics of aging. Since physical activity is effective in controlling the psychological and somatic symptoms which are part of the general symptomatology of aging male, the benefits of this behavior are also effective for the aging general score having presented lower prevalence among those men who were active when compared with the physically inactive, since the general score is partly a consequence of these two symptoms.…”
Section: Discussionmentioning
confidence: 99%